Soil organic carbon, physical fractions of the macro-organic matter, and soil stability relationship in lacustrine soils under banana crop. - Tatiana Rondon; Rosa Mary Hernandez; Manuel Guzman (PLoS ONE)
Banana is a staple food and a major export commodity in the tropics. However, banana production systems are affected by the plant-soil relationships, where properties such as quality and quantity of soil organic matter play an important role in the dynamics of soil physical properties. In order to evaluate the effect of the soil organic carbon (SOC) content and its distribution in the water-stable of soil aggregates (WAS), and the physical fractions of the macro-organic matter, a study was conducted in lacustrine soils under Banana cv. 'Grand Nain' in Venezuela. Soil sampling was carried out in two batches differentiated by their textural class and crop production. A completely randomized design under a directed random sampling technique was carried out. In each condition, 12 composite samples were taken at depths 0-5 and 5-10 cm, respectively. WAS were separated into micro (< 250 μm) and macroaggregates (> 250 μm). Also, physical fractionation by size-density of the macro-organic matter into light (LF), intermediate (IF), and heavy (HF) fraction using a silica gel solution, and SOC, were determined and correlated with banana yield and other agronomic traits. A major proportion of aggregates > 250 μm were found in both conditions and depths. Organic Carbon within soil aggregates ranged between 29.7 and 35.3 g kg-1. The HF was superior to IF and LF; however, its C content was higher in the LF. The results allow inferring that the stability conferred to these soils is primarily associated with the presence of the snail, which shares the same size as the aggregates studied. High yields are associated with high C content in stable aggregates, as well as in the most labile fractions of macro-organic matter. These results highlight the importance of the use of organic fertilizers less recalcitrant as a strategy for sustainable management of banana cultivation.